Numerical Simulation of The Magnetic Levitation System in State-Space Form - Opa Mustopa; Sovian Aritonang (Journal of Engineering and Scientific Research, 2022)
The maglev system is a technology that uses the repulsive force between magnets to float or levitate an object or vehicle. Maglev trains use electromagnets to counter the gravitational force of an object, so that the object can float in the air. With this technology, the resulting loss between the workpiece and the base can be eliminated. The technology used in this train is Electromagnetic Suspension (EMS). The research began by modeling the maglev system in the form of state space. Furthermore, the stability system model that has been built is analyzed. Finally, it is analyzed how the numerical simulation of an open loop without control is analyzed. The result of this research is that the floating system (maglev) is an unstable system if it is run in an open loop, so the maglev system requires sensors and controls in its operation.